Impact of zinc deficiency on mortality risk in patients with chronic obstructive pulmonary disease: a retrospective analysis - Chen, I-Wen; Yu, Ting-Sian; Lai, Yi-Chen; Liu, Ping-Hsin; Chang, Ying-Jen; Wu, Jheng-Yan; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Although nutritional deficiencies are increasingly recognized as modifiable factors in COPD progression, the relationship between zinc status and clinical outcomes remains poorly understood. This study examined the association between zinc deficiency and clinical outcomes in patients with COPD.MethodsWe conducted a retrospective cohort study using the TriNetX Research Network to analyze patients aged ≥18 years with established COPD, who underwent zinc testing between January 2010 and June 2023. Patients were categorized into zinc deficiency (serum zinc <70 μg/dL) and control groups (70–120 μg/dL). Using 1:1 propensity score matching, we created balanced cohorts controlling for demographics, comorbidities, and medications. The primary outcome was 6-month mortality, whereas secondary outcomes included COPD exacerbations, pneumonia, intensive care unit (ICU) admissions, hospital admissions, and hyperglycemic episodes. We also analyzed the impact of severe zinc deficiency (<50 μg/dL) and high zinc levels (>120 μg/dL) on prognosis.ResultsAfter matching, 3,525 patients were included in each group. Zinc deficiency was associated with a significantly increased 6-month mortality risk (hazard ratio [HR]: 1.94, 95% confidence interval [CI]: 1.49–2.52, p < 0.001). The secondary outcomes demonstrated consistent patterns of increased morbidity, including higher risks of pneumonia (HR 1.24; p = 0.031), hyperglycemia (HR 1.28; p < 0.001), ICU admission (HR 1.61; p < 0.001), and hospital admission (HR 1.28; p < 0.001), with no significant difference in the risk of COPD exacerbations. Severe zinc deficiency exhibited dose-dependent effects, with markedly elevated risks across all outcomes. Interestingly, high zinc levels were also associated with increased mortality (HR, 1.74; p = 0.005), suggesting a U-shaped relationship between zinc status and mortality risk.ConclusionZinc deficiency represents a significant and independent risk factor for mortality and morbidity in patients with COPD, with evidence of dose-dependent effects and a U-shaped risk relationship. These findings suggest that assessing and optimizing zinc status may represent an important yet under-recognized component of comprehensive COPD management strategies.